Anti–neurofascin-155 IgG4 antibodies prevent paranodal complex formation in vivo - Manso, Constance (J Clin Invest, 2019)
Neurofascin-155 (Nfasc155) is an essential glial cell adhesion molecule expressed in paranodal septate-like junctions of peripheral and central myelinated axons. The genetic deletion of Nfasc155 results in the loss of septate-like junctions and in conduction slowing. In humans, IgG4 antibodies against Nfasc155 are implicated in the pathogenesis of chronic inflammatory demyelinating polyneuropathy (CIDP). These antibodies are associated with an aggressive onset, a refractoriness to intravenous immunoglobulin, and tremor of possible cerebellar origin. Here, we examined the pathogenic effects of patient-derived anti-Nfasc155 IgG4. These antibodies did not inhibit the ability of Nfasc155 to complex with its axonal partners contactin-1 and CASPR1 or induce target internalization. Passive transfer experiments revealed that IgG4 antibodies targeted Nfasc155 on Schwann cell surfaces, and diminished Nfasc155 protein levels and prevented paranodal complex formation in neonatal animals. In adult animals, chronic intrathecal infusions of antibodies also induced the loss of Nfasc155 and of paranodal specialization and resulted in conduction alterations in motor nerves. These results indicate that anti-Nfasc155 IgG4 antibodies perturb conduction in the absence of demyelination, validating the existence of paranodopathy. These results also shed light on the mechanisms regulating protein insertion at paranodes.